The Relationship Between Pregnancy, Age, And Parity With The Incidence Of Anemia At The Pancur Health Center In Serang City In 2022 - Elis Lamasari; Omega DR Tahun (CV. Inara, 2023)
Data from the Serang City Health Office in 2021 there are 524 pregnant women in Serang City and of all these pregnant women there are 124 women who experience anemia. In the city of Serang there are 16 health centers where the Pancur Health Center has a high incidence of anemia in pregnant women (23.6%). To determine the relationship between pregnancy spacing, age, and parity with the incidence of anemia at Pancur Public Health Center, Serang City in 2022. Using an analytic method with a cross sectional approach. The population in this study were pregnant women in the working area of the Pancur Health Center, Serang City in 2022, namely 36 people. The sample in this study used a total sampling technique, namely the entire population was taken as a sample, namely 36 pregnant women who met the inclusion and exclusion criteria. There is a significant relationship between pregnancy spacing (p-value 0.001) and parity (p-value 0.002) with the incidence of anemia at Pancur Health Center, Serang City in 2022. There is a significant relationship between the distance between pregnancies and age and the incidence of anemia at Pancur Health Center, Serang City in 2022. For pregnant women, they should always check the health of their mothers and their wombs regularly during pregnancy and routinely attend counseling delivered by health workers. always take care of pregnancy such as fulfilling nutrition and diligently consuming iron tablets.